STRATEGI PEKERJA SOSIAL DALAM MENANGANI CHILD ABUSE DI PANTI SOSIAL MARSUDI PUTRA PARAMITA MATARAM - Mardiana Ulfa (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2018)
The act of child abuse often occurs in children because of low economic actors so that the protection, education, health, and basic needs of a child being neglected. Children who experience, witness and experience abuse directly experience traumatic conditions, where the trauma is in the form of psychological trauma that is embedded in the child’s subconscious. Often children who are victims of violence will have prolonged psychological disorders, for children who are victims will usually form a bad self-image, diffcult to trust other people, experience excessive fear, have no life expectancy, depression, stress and desire - suicidal desire. The strategy of social workers in handling child abuse at the Marsudi Putra Paramita Mataram social institution is to use the casework and group work method. In the casework method social workers carry out counselling as an alternative problem solving and help children who are victims of violence solve their problems through the stages of counselling. Whereas the groovy work method of social workers at the Marsudi Putra Paramita Social Institution in Mataram uses a religious approach as a technique to restore the healthy mentality of children who are victims of violence. In addition to the religious approach, social workers also provide social guidance as a provision for children’s behaviour to be accepted by the community. Social workers with a group approach aim to restore the social and psychological functions of child victims of violence to form groups such as skill groups, discussion groups and skill groups as a way for children to reduce stress and trauma through positive activities.